Penerapan Terapi Mendengarkan Murottal Al-Qur’an Untuk Kestabilan Emosi Klien - Anna Maria Manisei; M. Amin Sihabuddin; Neni Noviza (Journal of Society Counseling, 2023)
This study is entitled “The Application of Listening to Murottal Al-Qur’an Therapy for Client Emotional Stability at the Ar-Rahman Drug Rehabilitation Center Foundation”. This research is motivated by clients who use drugs who use drigs whose emotions are unstable, so they often express emotions excessively and are not in accordance with social values. The application of this therapy will provide a sense of relaxation and cause the brain to emit theta a snse of calm. The aim of the study was to describe the emotional stability of clients at YPRN Ar-Rahman and to find out the application of murottal Al-Qur’an listening therapy. The method used is a qualitative approach. Types of field research. The research subjects of 3 clients at YPRN Ar-Rahman according to the researcher’s criteria. Data collection tools through observation, interviews, and documentation. The data analysis technique used is data presentation, drawing conclutations. The results of this study indicate that: 1)the emotional stability of clients at YPRN Ar-Rahman of the three research subjects, there are 2 clients whose emotions are unstable, and the only client whose emotions are quite stable. 2)the application of listening therapy to murottal Al-Qur’an with surah Ar-Rahman for 20 minutes with 4 meetings is able to provide emotional stability ti research subjects. Key words: Listening Therapy to Murottal, Emotional Satbility.